Keperluan Latihan Untuk Penyelia: Satu Kajian Kes Di Sebuah Industri Hotel Di Kuching, Sarawak - Koh, Eng Chiang (Universiti Malaysia Sarawak, (UNIMAS), 1997)
The purpose of the study is to obtain information on training needs analysis for supervisor and the dimension for training in Hotel XYZ, an international organization in Kuching, Sarawak. This research examines the training needs for supervisory level from three different perspective: the perspective of supervisor, superior and subordinate. The training dimension consists of leadership, organizing and planning, delegating, developing people, teambuilding, motivating and communication. In this research, the researcher examines the relative importance of the seven training dimension from different perspective, and compares the differences between the perception of various respondent groups towards each dimension. The findings showed a higher level of need by the supervisors for training at supervisory level as compared to their superiors and subordinates. Besides, there are significant differences in the perception towards the organizing and planning dimension, teambuilding dimension and communication dimension between the supervisors and their subordinates. The findings from this study may provide guidelines for the management especially Human Resource practitioners in improving the training for supervisory level. It can be used as a base to arrange and organize a more complete and beneficial training program by giving more priority to some particular critical dimensio